Peningkatan Layanan Gizi bagi Pasien Covid-19 Di Instalasi Gizi RSUD Banyumas - Subardjo, Yovita Puri; Ramadhan, Gumintang Ratna; Betaditya, Dika (Universitas Nusantara PGRI Kediri, 2021)
The Corona Virus Disease (Covid-19) pandemic is currently a world problem, including Indonesia. Banyumas Hospital is one of the referral hospitals for Corona Virus Disease in the Banyumas Regency area. Over time there has been an increase in the number of Covid-19 patients being treated. Treatment of Covid-19 patients requires minimal contact between a nutritionist and a hospital food waiter with Covid-19 patients. A quick response is needed in the form of procurement of material tools to support this emergency. The aim of this program is to improve services needed by the Banyumas Hospital Nutrition Installation to provide optimal nutritional care to support the recovery of Covid-19 patients because the safety of health workers must be fulfilled by carrying out minimal contact with patients. The method carried out is in the form of to nutritionists for refreshing the development of science in the handling of Covid-19 patients in hospitals as well as providing the tools and materials needed for nutritional installations. The results obtained were refreshing the development of the science of handling Covid-19 patients, namely preventing malnutrition of Covid-19 patients, fulfilling the hydration of Covid-19 patients through providing electric kettles in isolation wards and providing bottled mineral water, providing disposable eating and drinking utensils to reduce potential transmission through eating utensils, as well as the fulfillment of tools in the form of Portable Wifi services for online nutrition counseling services to patients. The conclusion that can be taken is that the service provider plays a role in improving the nutrition services of the Banyumas Hospital Nutrition Installation in dealing with Covid-19 patients who are hospitalized at Banyumas Hospital.